Pengaruh Sanksi Pajak dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Yang Melakukan Usaha (Studi Kasus KPP Pratama Pare) - Faizatul Azizah (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
This research aimed to know how big the influence of tax sanction and tax socialization on taxpayer compliance of individuals who conducted business in KPP Pratama Pare. The population in this study are taxpayers of individuals who conduct business activities registered on KPP Pratama Pare. Based on data until the end of 2016 there are 43,769 individual taxpayers conducting business activities. Sampling method is simple random sampling with sample number 397 taxpayer. The results of simultaneous research Tax Sanctions and Socialization Taxation provide a significant effect on Personal taxpayer Compliance. Partially the tax sanction does not give a significant influence on Personal Taxpayer Compliance while Taxation Socialization gives negative and significant influence to Personal taxpayer Compliance. For the future efforts in implementing socialization should be increased with target and more intensive by KPP Pratama Pare and is expected to implement the enforcement of tax sanctions in accordance with applicable tax rules.